2013
DOI: 10.5009/gnl.2013.7.1.100
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of the Radiation Exposure Protection of Health Care Providers during Endoscopic Retrograde Cholangiopancreatography in Korea

Abstract: Background/AimsDuring endoscopic retrograde cholangiopancreatography (ERCP), all efforts should be made to be aware of radiation hazards and to reduce radiation exposure. The aim of this study was to investigate the status of radiation protective equipment and the awareness of radiation exposure in health care providers performing ERCP in Korean hospitals.MethodsA survey with a total of 42 questions was sent to each respondent via mail or e-mail between October 2010 and March 2011. The survey targeted nurses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…12,32 In the results about ERCP training of our survey, most ERCP already performed a national survey of radiation exposure protection and has reported the results of the survey in 2013. 33 The results of this previous survey are similar to those of our survey. However, the rate of respondents who have attended lectures or read documents on the 2009 ERCP-related radiation damage prevention recommendations of the KPBA was increased in our survey compared to that in the previous survey (from 40% to 75%).…”
Section: Radiation Protection During Ercpsupporting
confidence: 85%
See 2 more Smart Citations
“…12,32 In the results about ERCP training of our survey, most ERCP already performed a national survey of radiation exposure protection and has reported the results of the survey in 2013. 33 The results of this previous survey are similar to those of our survey. However, the rate of respondents who have attended lectures or read documents on the 2009 ERCP-related radiation damage prevention recommendations of the KPBA was increased in our survey compared to that in the previous survey (from 40% to 75%).…”
Section: Radiation Protection During Ercpsupporting
confidence: 85%
“…However, the rate of respondents who have attended lectures or read documents on the 2009 ERCP-related radiation damage prevention recommendations of the KPBA was increased in our survey compared to that in the previous survey (from 40% to 75%). 33 And considerable proportions of these respondents reported a changed awareness about radiation protection and an additional effort to improve the radiation protection. Therefore, a persistent nationwide promotion of the recommendations by KPBA would help to improve practice of radiation protection.…”
Section: Radiation Protection During Ercpmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, only 14% wore lead glasses during the procedure and 69% never wore it and the usage rates of mobile shields or lead curtains were only 14% and 24%, respectively 7. This propensity had not improved remarkably when a similar survey was conducted again in 2013 8. It would be possible to reduce this tendency by creating shielding barriers that are easy to use and have excellent protection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of many radiation protection equipment and techniques, the incorrect use, or the no usage at all, is a constant concern. Some studies have shown flaws in radiation protection practices since the staff did not know the correct way to use the equipment, did not have access to all necessary equipment or consider the equipment to be bothersome (SHIN et al, 2013). A 2011 survey on the radiation protection with Korean endoscopists showed that 75% do not monitor their radiation exposure.…”
Section: Evaluation Of Staff Exposurementioning
confidence: 99%